Efeito da LED terapia sobre parâmetros inflamatórios em modelo experimental de asma - Siqueira, Vanessa Perosino Cardoso (2016)
Asthma is a chronic inflammatory lung disease characterized by bronchoconstriction, elevated number of inflammatory cells in the airways such as eosinophils, neutrophils, lymphocytes, mast cells among others; increased mucus production and hyperresponsiveness. Considering that asthma may present more severe and resistant characteristics to conventional treatments, new therapies are of great importance. Phototherapy as Light-emitting diode (LED) has emerged as a treatment that presents good results for diseases which are characterized by inflammation. Thus, our objective was to investigate the effects of LED on the development of allergic lung inflammation. Male Balb/c mice were or not sensitized and challenged with ovalbumin (OVA) and treated or not with an LED therapy (1h and 4 h after each OVA challenge). Twenty-four hours after the last OVA challenge, analyzes were performed. We prioritized to analyze the total and differential cells present in bronchoalveolar lavage (BAL), blood and bone marrow, determination of mucus production, oedema, mast cell degranulation, and tracheal responsiveness. In addition, we investigated the levels of inflammatory and anti-inflammatory cytokines. Our results showed that LED treatment in asthmatic mice reduced the lung cell infiltration to the lung where can be observed by reduced number of both, total and differential cells (macrophages, lymphocytes and granulocytes). We also noted reduced number of eosinophils and neutrophils in the blood after LED treatment, and reestablishment of total cells found in the bone marrow. LED treatment did not alter the levels of inflammatory cytokines, but increased the levels of anti-inflammatory cytokines such as IL-10 and IFN-gamma. Moreover, LED treatment reduced mast cells degranulation, mucus production, oedema, and the tracheal contractile response. In conclusion, LED therapy reduced several important inflammatory parameters involved with worsening of asthma. Thus, this study may provide important information about the mechanisms involved in the LED effects on the respiratory tract, and in addition, it may open the possibility to a new approach for the treatment of asthma.